Characterising the burden of chronic kidney disease among people with type 2 diabetes in England: a cohort study using the Clinical Practice Research Datalink. Issue 3 (7th March 2023) - Cook, Sarah; Schmedt, Niklas; Broughton, Julie; Kalra, Philip A; Tomlinson, Laurie A; Quint, Jennifer K
Abstract : Objectives: To describe prevalence of chronic kidney disease (CKD), demographic and clinical characteristics, treatment patterns and rates of cardiovascular and renal complications for patients with type 2 diabetes (T2D) treated in routine clinical care. Design: Repeat cross-sectional study (6 monthly cross-sections) and cohort study from 1 January 2017 to 31 December 2019. Setting: Primary care data from English practices contributing to the UK Clinical Practice Research Datalink linked to Hospital Episode Statistics and Office for National Statistics mortality data. Participants: Patients with T2D aged >18 years, at least one year of registration data. Primary and secondary outcomes: Primary outcome was prevalence of CKD defined as chronic kidney disease epidemiology collaboration (CKD-EPI) estimated glomerular filtration rate <60 mL/min/1.73 m 2, and/or urinary albumin creatinine ratio ≥3 mg/mmol in the past 24 months. Secondary outcomes were prescriptions of medications of interest and clinical and demographic characteristics in the past 3 months. In the cohort study rates of renal and cardiovascular complications, all-cause mortality and hospitalisations over the study period were compared among those with and without CKD. Results: There were 574 190 eligible patients with T2D as of 1 January 2017 and 664 296 as of 31 December 2019. Estimated prevalence of CKD across the study period was stable at approximately 30%. Medication use was stable over time in people with CKD and T2D, with low use of steroidal mineralocorticoid receptor antagonists (approximately 4.5% across all time points) and a low use but steady increase in use of sodium-glucose co-transporter-2 inhibitors (from 2.6% to 6.2%). Rates of all complications were higher in those with CKD at the start of the study period, with increasing rates, with increased severity of CKD, heart failure and albuminuria. Conclusions: The burden of CKD in patients with T2D is high and associated with substantially increased rates of complications particularly in those with comorbid heart failure.